Implementasi Sistem Enterprise Resource Planning untuk Manajemen Proyek pada PT Delima Usaha Bersama - Evelyn Cindy Angela; Samosir, Ridha Sefina (Research and Community Service UNIVERSITAS KALBIS, 2024)
PT Delima Usaha Bersama is a service provider company in the field of Information Technology (IT Consultant). The work planning system at PT Delima Usaha Bersama uses Microsoft Excel, in result the work planning becomes non-effective. Furthermore, employees are inefficiently controlled caused by not having sufficient system for employee monitoring within all projects. Therefore, SOPlanning is used for implementing ERP system for project management to create a more effective and systematic employee work planning and performance control. The system implementation method uses the ASAP method and the type of research used is a case study. The result is an application for work planning and employee activity monitoring accessible through web with online connection.